TRANSFORMASI PEMBELAJARAN KEJURUAN MELALUI KURIKULUM MERDEKA: PERSPEKTIF MULTI-STAKEHOLDER DI BIDANG TEKNIK OTOMOTIF - Ramadhan, Gilang; Hidayat, Nuzul; Wagino, Wagino; Nanda, Iffarial (Ensiklopedia of Journal, 2025)
Abstract: The implementation of the Independent Learning Curriculum in Vocational High Schools requires comprehensive evaluation from direct users' perspectives to identify effectiveness and improvement areas. This study aims to analyze teachers' and students' perceptions of the Independent Learning Curriculum on Light Vehicle Engine Maintenance (PMKR) subjects at SMKN 1 Padang. The study employed a quantitative approach with survey method and descriptive design. Research subjects were 2 PMKR subject teachers and 46 students of grade XI Light Vehicle Engineering Program, selected using total sampling for teachers and proportionate stratified random sampling for students. Research instruments consisted of validated questionnaires with 5-point Likert scale. Data analysis used descriptive statistics with mean score calculations and interpretation categorization. Research findings show: (1) teachers' perceptions of the Independent Learning Curriculum on PMKR subjects are in "Good" category with mean score 3.69, with highest aspects in learning planning (4.38) and learning evaluation (4.25); (2) students' perceptions of PMKR learning with Independent Learning Curriculum are in "Very Good" category with mean score 4.33, with highest aspects in learning methods (4.66) and learning benefits (4.63); (3) there is a positive gap of 0.64 points with students having more positive perceptions than teachers. Research findings imply the importance of maintaining institutional support, enhancing project-based learning, and intensifying assessment system socialization for optimizing Independent Learning Curriculum implementation in vocational schools.Keywords: Independent Learning Curriculum, Teacher Perception, Student Perception, PMKR, Vocational High School, Vocational Learning.